2016
DOI: 10.1111/1467-9817.12074
|View full text |Cite
|
Sign up to set email alerts
|

University students vary their use of textese in digital messages to suit the recipient

Abstract: Background The casual, abbreviated writing style sometimes known as ‘textese’ (e.g., sorry im late ☹) has become widespread with the rise of digital communication. We explored Australian university students' views on, and use of, textese across three modalities (text message, Facebook post, email) and three recipient types (friends, peers, lecturers). Methods In Study 1, 51 undergraduates composed messages across the three modalities to the three recipient types. They also rated the appropriateness of messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, this contrasts with other studies in education contexts. Kemp and Clayton (2017) find that undergraduate students perceive abbreviations, that is 'textese', as inappropriate when used by staff.…”
Section: Introductionmentioning
confidence: 97%
“…However, this contrasts with other studies in education contexts. Kemp and Clayton (2017) find that undergraduate students perceive abbreviations, that is 'textese', as inappropriate when used by staff.…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that the majority of the grammatical violations seen in the messages in the current study may well have been deliberate. Such an interpretation is borne out by the results of recent work conducted by Kemp and Clayton (), who found through experimental work that undergraduate students were sensitive when to use textspeak and could vary their style of written communication in line with who was likely to read it. However, there is still room for further research to look at the extent of deliberate versus accidental grammatical errors in texting.…”
Section: Discussionmentioning
confidence: 99%
“…This may not only change the level of emotional engagement with the task, but also reveal important differences with regard to how the relationship between message sender and receiver can modulate emoji processing. Indeed, several prior studies have shown that undergraduate students rate the use of textese as more appropriate in messages to friends compared to teachers (Drouin & Davis, 2009; Kemp & Clayton, 2016; Kemp & Grace, 2017). As a result, further investigations may be necessary to provide more thorough insights into the links between sender ratings and eye movements on messages with and without emojis.…”
Section: Discussionmentioning
confidence: 99%